Stories of ourselves: the university of cambridge international examinations anthology of stories in english (Cambridge University Press Cambridge, 2008)
Stories of Ourselves is a set text for the Cambridge Literature in English courses at IGCSE, O Level, AS and A Level. The anthology contains stories by writers from many different countries and cultures.